Modifikasi Balok Beton Tulangan Komposit Guna Meningkatkan Daktilitas Pada Konstruksi Bangunan Gedung - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Marsudi, M. Tri Rochadi, Nur Setiaji P., Stefanus (Teknis, 2014)
Iron concrete is a product of mining whose existence will someday run out. To solve the probem, alternatively attempted use cheap bamboo reinforcement and high strength . In this study the bamboo used instead of tensile reinforcement in concrete beams is simple. Berlulangan planned beam (underreinforced). All casting bamboo beams torsion beams are given particular on its reinforcement. In the end you will know how much a modification beams with tensile reinforcement of bamboo piinan petung in resist bending style. The results showed that the quality of concrete plans K - 225 kg/cm2 obtained an average compressive strength is 229 kg/cm2. Tensile strength of concrete iron test while 33.5 kN to 17.5 kN Babbu torsion. Flexural strength testing of concrete beams reinforced bamboo strands pull 35 kN, while for tensile steel reinforcement ï 10 mm concrete compressive strength was stopped after reaching an average of 81 kN. Concrete composite beams with tensile reinforcement of bamboo strands petung building materials can be used as a substitute for steel reinforcing.Key Word : Concrete Beams, Reinforcement bamboo, strong bending